Keanekaragaman Mamalia Kecil Pada Empat Tipe Tutupan Lahan Di Kesatuan Pengelolaan Hutan (KPH) Batutegi, Provinsi Lampung - Putra, Albar Bagas; Darmawan, Arief; Dewi, Bainah Sari; Fitriana, Yulia Rahma; Febryano, Indra Gumay (MAKILA, 2022)
The diversity of small mammals has a vital role as a bioindicator of a managed area in the forest. This research was conducted to determine the small mammals in four types of land cover in the agroforestry management area of ​​KPH Batutegi. Sampling was carried out using traps in the four types of land cover. Species diversity was analyzed by diversity index, evenness, dominance, and abundance. The results of this study indicate that the variety, evenness, and abundance of small mammals are low due to land cover conditions, elevation, and the behavior of small mammals in their habitat. The dominant small mammals are Rattus tiomanicus sabae and Maxomys baeodon because they have a high level of adaptation to various habitats. Twelve small mammals were found in the agroforestry cover, ten individuals in the forested cover, four individuals in the monoculture coffee cover, and two individuals in the private land. The management of the Batutegi KPH shall counsel the community to prevent land clearing, which causes damage to forest sustainability, to maintain the existence of small mammals.